Medical segetal flora of Central Poland - Warcholińska, Aurelia Urszula (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2008)
In the paper a list and general characterization of medical segetal flora of Central Poland is given. This flora consists of 300 taxa. Among the most threatened species there are 6 taxa: Adonis aestivalis, A. flam mea, Anagallis foemina, Bupleurum rotundifolium, Camelina saliva, Cuscuta europaea.